2000
DOI: 10.1118/1.598844
|View full text |Cite
|
Sign up to set email alerts
|

A model for photon detection and dosimetry with superheated emulsions

Abstract: A model is presented for the analysis and prediction of the photon response of detectors based on superheated emulsions of light halocarbons in tissue equivalent gels. It is shown that on the basis of a nondimensional thermodynamic quantity, called reduced superheat, it is possible to identify the degree of superheat, or the operating temperature, corresponding to the photon sensitization of the emulsions. Moreover, on the basis of the mass energy absorption coefficients, it is possible to determine the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…In this work we have observed that R404A is gamma ray sensitive at and above 13.3 o C at one atmospheric pressure. This agrees with the empirical model by d'Errico et al [24]. We also observed that R404A shows a strong presence of the second metastable state.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this work we have observed that R404A is gamma ray sensitive at and above 13.3 o C at one atmospheric pressure. This agrees with the empirical model by d'Errico et al [24]. We also observed that R404A shows a strong presence of the second metastable state.…”
Section: Discussionsupporting
confidence: 93%
“…From Fig. 4, it is observed that the R404A liquid becomes sensitive to 662 keV gamma rays at about 13.3 o C. The obtained gamma ray threshold for 137 Cs is in good agreement with the proposed empirical model by d'Errico et al [24,25], which predicts the threshold to be immediately above the mid-point between boiling and critical temperatures of the halocarbons. According to this model the threshold for R404A, having the boiling point and critical point of -46.…”
Section: Experiments For Study the Gamma Ray Sensitivity Of The R404a...supporting
confidence: 85%
“…The gamma-ray induced nucleation was studied using 0.5 Ci 241 Am and 0.02 Ci 137 Cs gamma-ray sources. It is observed earlier that for 241 Am and 137 Cs gamma-ray sources the gamma-ray sensitive threshold temperature for R-12 is about 38.5 o C and 42.5 o C respectively[5][6]. Since R-12 detector is insensitive to 137 Cs gamma-ray source at 40.5 o C the pulse shape data for 137 Cs gammaray source were acquired at about 44.5 o C and for 241 Am gamma-ray source the data were acquired at 5 about 40.5 o C and 44.5 o C. The detector sensitivity in terms of the number of events per 10 µSv neutron and gamma-ray dose at 40.5 o C and 44.5 o C are shown infigure 2.…”
mentioning
confidence: 84%
“…A superheated droplet detector (SDD) [1,2] consists of a large number of micron sized superheated liquid droplets dispersed in a viscoelastic gel [1] or in a soft polymer [2] medium. SDD is known to be able to detect neutrons [3,4], gamma-rays [5,6] and other charged particles [7,8] under certain operating temperature and pressure [5,9]. In SDD, each droplet can be considered as a micron size bubble chamber [10][11][12], where a drop vaporizes when sufficient energy is deposited by the energetic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…These detectors are used for the detection of neutrons, charged particles, gamma-rays etc. [2][3][4][5]. The SDD and BD are threshold type detectors where by changing the operating temperature and/or pressure the threshold can be controlled [2].…”
Section: Introductionmentioning
confidence: 99%